RELATIONSHIP OF VEIN AND DISSEMINATED GOLD MINERALIZATION AND THE LOCAL GEODYNAMICS OF ORE FIELDS - Kalinin A.I. (My University, 1990)
Vein deposits, the traditional source of gold, have been known for a very long time. In addition, however, disseminated ores of stratiform and other 'large-volume' ore deposits have recently become increasingly significant. The problem of the relationship between the vein and disseminated gold ores, whether lying in a single ore field or a considerable distance apart, besides its purely scientific aspect is also of clear economic significance, since it has a direct bearing on the development of criteria for the prediction, prospecting for and appraising gold mineralization. Using a combination of geologic criteria such as the general style of structure of ore fields and deposits, the kinematic type of the ore-bearing elements and the distinctive structures and textures of the ores, especially any signs of their intramineralizational recrystallization, I have been able to establish that the ore stage in the deposits of various gold-ore associations has occurred under regimes of compression, extension and pulsation, the latter occurring episodically. The interaction of the regional and the local regimes is determined by the universality of compression, which gives way to extension only in separate, relatively brief intervals and in separate places. When no such change in regime takes place, the ores are deposited under conditions of compression that has inherited the regional geodynamic background.